Human Resources Development in the Context of Improving Service Quality at the West Sebatik Sub-district Office, Nunukan Regency, North Kalimantan Province - lilisnawati; Ismail Rasulong; Sri Andayaningsih (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the development of human resources (HR) in improving the quality of public services at the West Sebatik Sub-district Office, Nunukan Regency, North Kalimantan Province. The research uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The research informants amounted to nine people who were selected using purposive sampling techniques, consisting of elements of leaders, employees, and service recipients. Data analysis was carried out using the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that human resource development through continuous training and coaching plays an important role in improving the competence of apparatus, especially in mastering digital-based service technology. The quality of public services at the West Sebatik Sub-district Office is considered good, which is shown by the attitude of the apparatus who are professional, responsive, friendly, and able to provide clear service information to the community. The use of information technology and social media also supports the effectiveness of services. However, there is still a discrepancy between the educational background of employees and the positions they occupy, so it requires more targeted competency development. The level of public satisfaction with services is very good, as evidenced by the value of the Community Satisfaction Survey (SKM) which continues to increase from 90.83 in 2024 to 90.94 in 2025. Thus, sustainable human resource development has been proven to make a positive contribution to improving the quality of public services in border areas.